2013
DOI: 10.4490/algae.2013.28.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and molecular characterization of the epiphytic dinoflagellate Amphidinium massartii, isolated from the temperate waters off Jeju Island, Korea

Abstract: Amphidinium massartiiBiecheler is an epiphytic and toxic dinoflagellate. Prior to the present study, A. massartii has been reported in the waters off the Mediterranean, Australian, USA, and Canadian coasts. We isolated Amphidinium cells from the coastal waters of Jeju Island, Korea and their morphology and rDNA sequences indicated that they were A. massartii. Herein, we report for the first time the occurrence of A. massartii in the waters of the temperate region in the northwestern Pacific Ocean. The large su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Jeong et al (2012b) therefore suggested that the Korean strain of C. canariensis was closely related to the two Atlantic strains and the as its overall shape and body scales, coincides with that of an A. massartii strain isolated from Australia (Murray et al 2012. Moreover, the sequences of 5.8S, ITS2, and cytochrome b of Korean A. massartii strains (AMJJ1, AMJJ2, and AMJJ3) were identical with those of the Australian A. massartii CS-259 (Lee et al 2013). Recent phylogenetic and toxicity analyses conducted by Karafas et al (2017) suggested that the strains in the nontoxic A. massartii clade 1 and the toxic A. cf.…”
Section: Coolia Sppmentioning
confidence: 62%
See 1 more Smart Citation
“…Jeong et al (2012b) therefore suggested that the Korean strain of C. canariensis was closely related to the two Atlantic strains and the as its overall shape and body scales, coincides with that of an A. massartii strain isolated from Australia (Murray et al 2012. Moreover, the sequences of 5.8S, ITS2, and cytochrome b of Korean A. massartii strains (AMJJ1, AMJJ2, and AMJJ3) were identical with those of the Australian A. massartii CS-259 (Lee et al 2013). Recent phylogenetic and toxicity analyses conducted by Karafas et al (2017) suggested that the strains in the nontoxic A. massartii clade 1 and the toxic A. cf.…”
Section: Coolia Sppmentioning
confidence: 62%
“…in the coastal waters of Jeju Island. Later, detailed morphological and molecular characteristics of Amphidinium massartii were revealed through SEM and phylogenetic analyses (Lee et al 2013). The morphology of the Korean strain A. massartii AMJJ1, such East Sea of Korea.…”
Section: Prorocentrum Sppmentioning
confidence: 99%
“…Fixed samples were washed three times in 1.5 mL of 5 • C ultrapure water and centrifuged at 3000× g (4 • C) for 5 min. The cells then underwent a graded ethanol (EtOH) dehydration series (10,20,30,40,50,60, 70, 80, 90, and 99%; 1.5 mL each). At every step, the cells were gently resuspended for 1 min and centrifuged under the previous conditions, and the supernatant was discarded.…”
Section: Cell Morphology and Statistical Analysismentioning
confidence: 99%
“…The rDNA sequences of the two species were identical to those of the Korean strain (Ostreopsis cf. ovata [52]; Amphidinium massartii [53]).…”
Section: Dna Extraction and Species Identificationmentioning
confidence: 99%